The Effect of Job Satisfaction on Organizational Commitment and Work Discipline - Tutik Winarsih; Fariz Fariz (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study examined the effect of job satisfaction on organizational commitment and discipline of work, as well as determined the effect of organizational commitment to the discipline of work. This study involved the lecturers of STIE YAPAN Surabaya. Data analysis that was used in this research was the analysis of the path (path analysis) where confirmatory factor analysis was conducted previously to confirm the indicators that described the construct or variable. The results of confirmatory factor analysis proved that all of the indicators used in this study were not deleted and all the indicators were able to explain the variable job satisfaction, organizational commitment and work discipline. The results of path analysis (path analysis) explained that satisfaction effects on organizational commitment, commitment affects the discipline, and job satisfaction affects work discipline. Theoretical implication of this study is that the study supports the theory that when the lecturers feel more satisfied, they will be more commit and discipline. The practical implications of this study are expected to be a material consideration to STIE YAPAN Surabaya foundations in policy and decision making related to job satisfaction, organizational commitment and work discipline. The advice that can be given to the foundation is increasing attention to the dimensions of salary, normative commitment, and discipline work as dimensions that have bad perception.